Mixed Lubrication Modeling of Multi-Lip Reciprocating Seals Based on Elastohydrodynamic Lubrication Theory - Donghong Cheng; Lichen Gu; Yu Sun (Machines, 2022)
Multi-lip reciprocating seals are extensively used in the subject of engineering equipment. However, the current research on the tribology of reciprocating seals mainly focused focuses on the numerical analysis of single-lip seals. In order to study the sealing performance of multi-lip seals, this paper takes double-acting seal (DAS) as the research object, and establishes a multi-lip mixed elastohydrodynamic lubrication (M-EHL) numerical simulation model from the perspective of solid mechanics, fluid mechanics, contact mechanics, and deformation mechanics. The sealing characteristics under different working conditions (sealed pressure, piston rod extension speed, and seal surface roughness) were analyzed by numerical calculation, and the variation trend of friction force corresponding to the experimental results was obtained. The model can provide a modeling guidance basis for the M-EHL characteristic analysis and structural optimization design of multi-lip reciprocating seals in the mechanical field.